Physical Computing and its Scope - Towards a constructionist Computer Science Curriculum with Physical Computing - Przybylla, Mareen; Romeike, Ralf (Constructionism and Creativity. Proceedings of the 3rd International Constructionism Conference 2014, 2014)
Physical computing covers the design and realization of interactive objects and installations and allows students to develop concrete, tangible products of the real world, which arise from the learners' imagination. This can be used in computer science education to provide students with interesting and motivating access to the different topic areas of the subject in constructionist and creative learning environments. To make many existing activities and examples of such project ideas available for classroom use and to expand the topic areas suitable for learning in such environments beyond introductory to programming, a physical computing syllabus for computer science courses in general education schools has been developed. In this paper the methods and different perspectives that were taken into account are presented. The resulting syllabus can be used to develop a constructionist computer science curriculum with physical computing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.didain.physic
Keywords: Computer science education; Constructionist learning; Physical computing; Syllabus